Volume 3: Heat Transfer, Parts a and B 2006
DOI: 10.1115/gt2006-90532
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Velocity Profiles for Effusion Cooling of a Combustor Liner

Abstract: Effusion cooling of combustor liners for gas turbine engines is quite challenging and necessary to prevent thermal distress of the combustor liner walls. The flow and thermal patterns in the cooling layer are affected by the closely spaced film-cooling holes. It is important to fully document how the film layer behaves with a full-coverage cooling scheme to gain an understanding into surface cooling phenomena. This paper discusses experimental results from a combustor simulator tested in a low-speed wind tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For a single-walled effusion liner without dilution jets, Scrittore et al [10] found that the velocity profiles and turbulence levels of the effusion jets scaled with the blowing ratio of the effusion jets. In addition, they found that once the flow was fully developed, the momentum flux ratio of the effusion jets did not affect the penetration height.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…For a single-walled effusion liner without dilution jets, Scrittore et al [10] found that the velocity profiles and turbulence levels of the effusion jets scaled with the blowing ratio of the effusion jets. In addition, they found that once the flow was fully developed, the momentum flux ratio of the effusion jets did not affect the penetration height.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…Conceming the investigation of combustor typical effusion cooling schemes, Scrittore et al [7,8] conducted studies on velocity profiles along an effusion cooled liner and about the effect of combustor typical features like dilution jets on the cooling effectiveness. These studies show that the streamwise velocity and turbulence level directly scale with the blowing ratio and that a full-coverage effusion cooling develops into a fully-developed velocity profile at a nominal location of 15 film-cooling hole rows downstream.…”
Section: Related Past Investigationsmentioning
confidence: 99%
“…An interesting attempt to characterize the effects of the swirled flow on combustor heat transfer is conducted by Patil et al [11] which, studying an air spray nozzle with a swirl number of 0.7, pointed out how increasing Reynolds number does not change the position of the peak in heat flux due to the impingement of the swirl flow on the liner, whereas the intensity of the peak is reduced. However, as already mentioned, most studies devoted to effusion cooling deal with flat plates which have been quite exten sively studied both singularly and with additional cooling features such as impingement jets [12,13], slot cooling [14], and dilution holes [15,16]. Focusing on effusion systems only, Behrendt et al [4] showed that shallow angles promote cooling effectiveness due to reduced jet penetration and increased heat removal within the perforations.…”
Section: Introductionmentioning
confidence: 98%